ANALISIS KOMPARASI KINERJA KEUANGAN BPR MILIK SWASTA DAN BPR MILIK PEMERINTAH DAERAH DI PROVINSI JAWA TENGAH PERIODE 2014-2016 - Widya Prananta; Yulianti Yulianti; Anita Damajanti (Jurnal Akuntansi Indonesia, 2019)
This study aims to analyze the Differences in Performance of Private Owned Rural Banks and Local Government-Owned Rural Banks in Central Java Province by using financial performance ratios namely Non Performing Loans (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR). ), Earning Assets Quality (KAP), Operating Income Operating Expenses (BOPO) and Return on Assets (ROA). The method used to analyze the data is the Different Test using the Independent T test. This study used the SPSS Version 19. Analysis tool.The population used in this study was BPR in Central Java. The sample of this study is the Rural Bank owned by the Central Java Regional Government and the Private Rural Banks in Central Java Province. Sample selection using purposive sampling. Based on the Independent Test of the T test, there are differences in the NPL and KAP ratios between the Regional Government-owned BPR and the Private BPR, while there are no differences in the CAR, LDR, BOPO and ROA ratios.